Thoracic synovial cyst as cause of cord compression in a patient with Charcot-Marie-Tooth disease - De Mauro, Domenico; Cicia, Alessandra; Meluzio, Maria Concetta; Grillo, Giovanni; Smakaj, Amarildo; Perna, Andrea; Tamburrelli, Francesco Ciro (Acta Biomedica Atenei Parmensis, 2023)
An 80-year-old male patient affected by Charcot-Marie-Tooth (CMT) disease came to our attention in July 2020, for the occurrence of low back pain and lower limb weakness, and also saddle anesthesia, urinary and faecal retention were referred. His diagnosis of CMT is dated back to 1955 and through the years, the clinical picture slowly worsened but never got particularly severe. The quick symptoms outbreak and the presence of urinary disturbances were red flags, which lead us to direct the diagnostic orientation elsewhere. A Magnetic Resonance Imaging of the thoraco-lumbar spinal cord was then performed and it was suggestive for synovial cyst at T10-T11. The patient underwent a decompression with laminectomy and then stabilized through arthrodesis. In the very next days after the surgery, the patient showed a sudden and significant improvement of his condition. At the last visit, he showed a remarkable relief of the symptoms, walking by himself.